Study of management of construction waste material in residential project in Malaysia: a review - Sutaji, Hadri Safwan; Haron, Nuzul Azam; Ales@Alias, Aidi Hizami; Hassim, Salihudin; Raja Ahmad Effendi, Raja Ahmad Azmeer (Inderscience Publishers, 2022)
The construction industry can be classified as one of the major contributors to the development of Malaysia. Over the years, rapid development in terms of building and infrastructure in Malaysia shows that Malaysia is moving towards a developed country. However, with the increase of construction projects in Malaysia, this is also increasing the production of construction waste material at site which then will contribute to environmental pollution. The 3-R concept seems most practised on site to reduce the construction waste material even though it has some disadvantages. In fact, the reason why the majority of contractors in Malaysia do not want to implement the good and right construction waste management is due to willingness to pay for the waste management at site. Thus, site waste management plan (SWMP) is one of the new methods that can be implemented to manage the construction waste on site.